An alternative approach for determining suction of polyethylene glycols for soil testing. Issue 1 (2nd December 2019) - Lieske, W.; Tripathy, S.; Baille, W.; Schanz, T.
Abstract : Determination of suction of polyethylene glycol (PEG) is vital for unsaturated laboratory testing that uses the osmotic technique to study the hydromechanical behaviour of fine-grained soils. To date, suctions of PEG solutions have been either experimentally measured or calculated from established semi-empirical relationships between the concentration of PEG and the suction. This paper presents an alternative approach for determining suctions of aqueous PEG solutions based on a modified Flory–Huggins equation. Using the proposed method, suctions of various PEGs can be precisely calculated by knowing the average molar mass, concentration of the solution and an interaction coefficient, which represents the quality of the PEG–solvent interaction. The suggested method relies on the  characteristics and thermodynamical behaviour of PEGs in solution. Experimental data of several PEG–water mixtures reported in the literature were analysed. The superiority of this approach remains with the abilities to verify the molar mass of PEGs and estimate the suctions of PEG at high concentrations.